Use of a cervical stent for long‐term treatment of pyometra in the mare: A report of three cases. Issue 8 (26th June 2019) - Krohn, Judith; Ennen, Sophia; Hospes, Rainer; Nieth, Jennifer; Wehrend, Axel
Abstract: An effective long‐term treatment is necessary for mares with pyometra, because the condition tends to recur. In many affected animals, several conformational or anatomical anomalies contribute to impaired uterine clearance. Ovariohysterectomy is the surgical procedure of choice. Conservative therapy consists of draining and flushing the uterus, and systemic anti‐inflammatory and antimicrobial treatment. Uterine secretions tend to accumulate again after local treatment, especially in mares with poor vaginal conformation or cervical adhesions. Herein, we describe three cases in which a cervical stent was used in mares after mechanical or manual dilation of the cervix to achieve permanent draining of the uterus. The mares remained symptom‐free for up to 6 years and exhibited good clinical progress and good performance in competitions. Potential complications of the procedure include loss of the stent and obstruction caused by viscous secretion. A cervical stent is a relatively easy and low‐cost option for the long‐term treatment of pyometra in mares, particularly in cases where excessive costs of surgery and risks of a general anaesthesia are to be avoided.